Comparative effectiveness of torasemide versus furosemide in symptomatic therapy in heart failure patients: Preliminary results from the randomized TORNADO trial - Balsam, Paweł (Cardiol J, 2020)
BACKGROUND: Recent reports suggest that torasemide might be more beneficial than furosemide in patients with symptomatic heart failure (HF). The aim was to compare the effects of torasemide and furosemide on clinical outcomes in HF patients. METHODS: This study pilot consisted of data from the ongoing multicenter, randomized, unblinded endpoint phase IV TORNADO (NCT01942109) study. HF patients in New York Heart Association (NYHA) II–IV class with a stable dose of furosemide were randomized to treatment with equipotential dose of torasemide (4:1) or continuation of unchanged dose of furosemide. On enrollment and control visit (3 months after enrollment) clinical examination, 6-minute walk test (6MWT) and assessment of fluid retention by ZOE Fluid Status Monitor were performed. The primary endpoint was a composite of improvement of NYHA class, improvement of at least 50 m during 6MWT and decrease in fluid retention of at least 0.5 Ω after 3-months follow-up. RESULTS: The study group included 40 patients (median age 66 years; 77.5% male). During follow-up 7 patients were hospitalized for HF worsening (3 in torasemide and 4 in furosemide-treated patients). The primary endpoint reached 15 (94%) and 14 (58%) patients on torasemide and furosemide, respectively (p = 0.03). CONCLUSIONS: In HF patients treated with torasemide fluid overload and symptoms improved more than in the furosemide group. This positive effect occurred already within 3-month observation.